KONTRIBUSI DISIPLIN BELAJAR DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR KKPI SISWA KELAS X TKJ SMK NEGERI 1 BENDAHARA - Zulfadli Zulfadli; Titi Sriwahyuni; Thamrin Thamrin (Universitas Negeri Padang, 2016)
The purpose of this study is to reveal the contribution of the discipline of learning and school environment on learning outcomes KKPI subjects in class X TKJ SMK Negeri 1 Bendahara. This type of research is descriptive correlation. The population in this study were all students of class X TKJ SMK Negeri 1 Bendahara, consists of two classes totaling 66 people. Random sampling technique that is proportional random sampling. Data obtained from the student learning outcomes KKPI subject teachers of SMK Negeri 1 Bendahara. While data on the discipline of learning and the school environment collected through questionnaires using likert scale that has been tested for validity and reliability. Data was analyzed using statistical methods with the help of software Microsoft Excel 2007. The result showed: (1) Discipline learning and school environment together contributed 24.89% to the learning outcomes of students of class X TKJ SMK Negeri 1 Bendahara; (2) Discipline learn contributed 10.24% to the learning outcomes of students of class X TKJ SMK Negeri 1 Bendahara; (3) The school environment contributed 10.18% to the learning outcomes of students of class X TKJ SMK Negeri 1 Bendahara. So it can be concluded that the Disciplinary learning and school environment contribute to the learning outcomes, the higher the better discipline of learning and school environment, the learning outcomes will be better. Keywords : Discipline of learning, school environment, Learning Outcomes, Descriptive correlation, Proportional random sampling.